Pengaruh Digital Marketing Dan Aksesibilitas Pelayanan Terhadap Kinerja Klinik Gigi Sultan Dental Care - Mubaraq Juli Saputra; Dasrun Hidayat; Rinawati; Rian Andriani (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2026)
Sultan Dental Care faces challenges in increasing visibility and attracting more patients through its newly implemented digital marketing strategy. With intense competition in the private clinic industry, an evaluation and optimization of digital marketing strategies, along with improved service accessibility, are necessary to enhance the clinic’s recognition and appeal to the public. This study aims to analyze the impact of digital marketing and accessibility on the performance of Sultan Dental Care Dental Clinic. The research employs a quantitative method, collecting data through questionnaires distributed to patients and clinic employees. The analysis results indicate that digital marketing does not significantly affect performance, whereas accessibility has a significant impact. This study provides insights for Sultan Dental Care Dental Clinic on the importance of improving accessibility to enhance employee performance. These findings can also be applied to other clinics to improve service quality for patients.